The Thief of Lanwyn Manor - Ladd, Sarah E. (Nashville, Tennessee : Thomas Nelson, 2020)
"Perfect for fans of Poldark, Sarah E. Ladd latest Regency romance, The Thief of Lanwyn Manor, explores Cornwall, England, and the secrets within one of its historic manor houses"--
Keywords: Man-woman relationships -- Fiction; Courtship -- Fiction -- 19th century -- England; Manors -- Fiction -- England; Copper mines and mining -- Fiction -- England; Brothers -- Fiction; Theft -- Fiction; Cousins -- Fiction; Cornwall (England : County) -- Fiction -- History -- 19th century; Romance fiction; Historical fiction; Religious fiction; Regency fiction